2010
DOI: 10.1103/physrevlett.104.095502
|View full text |Cite
|
Sign up to set email alerts
|

New Universality Class for the Fragmentation of Plastic Materials

Abstract: We present an experimental and theoretical study of the fragmentation of polymeric materials by impacting polypropylene particles of spherical shape against a hard wall. Experiments reveal a power law mass distribution of fragments with an exponent close to 1.2, which is significantly different from the known exponents of three-dimensional bulk materials. A 3D discrete element model is introduced which reproduces both the large permanent deformation of the polymer during impact, and the novel value of the mass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 19 publications
(34 reference statements)
4
71
0
1
Order By: Relevance
“…[8][9][10][11][12][13][14] This corresponds to a regime in which the fragment distribution has certain aspects of scale-invariance and can be treated as a fractal with a particular dimensionality. Oddershede and coworkers suggested that the power-law behavior observed in brittle fragment distributions could be interpreted in the context of self-organized criticality, and proposed a fragment distribution of the form,…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] This corresponds to a regime in which the fragment distribution has certain aspects of scale-invariance and can be treated as a fractal with a particular dimensionality. Oddershede and coworkers suggested that the power-law behavior observed in brittle fragment distributions could be interpreted in the context of self-organized criticality, and proposed a fragment distribution of the form,…”
Section: Introductionmentioning
confidence: 99%
“…It is however possible to use lower viscosities and thereby higher strain rates and re-scale the simulation time to match ice behaviour as long as the viscous flow timescale remains slow compared with that for fracture events (Riikilä et al, 2013). This approach is somewhat similar to the plasticity model used by Timar et al (2010). Another, simpler, approach to imitate viscous behaviour is to use a weak and short-range attraction force for particles that are close to being in contact, similar to cohesion models of wet granular materials (Huang et al, 2005).…”
Section: Modelmentioning
confidence: 99%
“…The exponent of the distribution was found to show a high degree of robustness, i.e., investigations revealed that the value of the exponent does not depend on the type of materials, amount of input energy, and on the way the energy is imparted to the system until materials of a high degree of heterogeneity are fragmented [1,9,10]. The value of the exponent is mainly determined by the dimensionality of the system [13,15,18,19,21,23,[25][26][27] and by the brittle or ductile mechanical response of the material [28]. The universality of fragmenting has been shown to be the fingerprint of an underlying phase transition from the damaged to the fragmented phase of the breakup process [5,6,14,18].…”
Section: Introductionmentioning
confidence: 99%